2023
DOI: 10.7150/thno.81938
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric magnetic resonance imaging for radiation therapy response monitoring in soft tissue sarcomas: a histology and MRI co-registration algorithm

Abstract: Rationale: To establish a spatially exact co-registration procedure between in vivo multiparametric magnetic resonance imaging (mpMRI) and (immuno)histopathology of soft tissue sarcomas (STS) to identify imaging parameters that reflect radiation therapy response of STS. Methods: The mpMRI-Protocol included diffusion-weighted (DWI), intravoxel-incoherent motion (IVIM), and dynamic contrast-enhancing (DCE) imaging. The resection specimen was embedded in 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In the literature [24,58,59] and previous works by our group [28][29][30][31][32][33][34]45], ctDNA is described as a potential biomarker for the prediction of STS, its recurrence, and minimal residual disease PLOS ONE after resection. However, it has not been shown if ctDNA can be used as a biomarker for therapy response and how ctDNA correlates with vital tumor mass during NRT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature [24,58,59] and previous works by our group [28][29][30][31][32][33][34]45], ctDNA is described as a potential biomarker for the prediction of STS, its recurrence, and minimal residual disease PLOS ONE after resection. However, it has not been shown if ctDNA can be used as a biomarker for therapy response and how ctDNA correlates with vital tumor mass during NRT.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we have developed a prospective study protocol that considers previous studies’ limitations and uses a highly sensitive and optimized NGS-based panel design for liquid biopsies. Combining this data with mpMRI and immunohistological findings of the resected tumor, large interdisciplinary data sets are generated to characterize the STS [ 45 ]. In addition, tumor response to NRT and morphological changes in the course of treatment can be monitored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional multiparametric magnetic resonance imaging (mpMRI) and 2-[ 18 F]fluoro-2-deoxy-D-glucose ( 18 F-FDG) PET/CT are two major methods to detect early metabolic responses after radiotherapy 39 , 40 . These imaging results as early predictors, such as apparent diffusion coefficient (ADC), magnetic resonance spectroscopy (MRS), standardized uptake value (SUV) and total lesion glycolysis (TLG), have been frequently explored in radiotherapy for a variety of tumor indications (e.g., esophageal cancer, soft tissue sarcoma) 41 , 42 . Furthermore, these imaging results in radiotherapy have been reported to be correlated with end points such as recurrence-free survival (RFS) or overall survival (OS) in several prospective/retrospective studies 43 - 45 .…”
Section: Molecular Imaging and Imaging Biomarkers For Cancer Radiothe...mentioning
confidence: 99%
“…Several approaches have been implemented to validate the in vivo images with histological slices [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Some authors suggested the use of the acquisition of the MRI or Computed Tomography (CT) ex vivo specimen as an intermediate step [ 11 , 15 , 16 , 17 , 18 , 19 , 23 , 25 , 26 ] since the histopathological specimen is acquired with the same contrast of the in vivo image, while maintaining the deformation due to resection of the histopathology images.…”
Section: Introductionmentioning
confidence: 99%